Ecomorfotipos de assembleias de peixes em diferentes escalas de impactos antrópicos. - Alves, Robson Senna de Andrade (2018)
Abstract: The objective of this study was to verify if ecomorphotype patterns respond to environmental variations at mesohabitat level. The hypothesis tested was that ecomorphotypes could be used as indicators of the mesohabitats and their environmental conditions. Thus, environmental and ichthyofunistic data were collected in three mesohabitats (riffle, run and pool) of ten streams (five inserted in rural and five in urban environments). Afterwards, 22 ecomorphologic indexes related to the trunk, fins, head, eyes and mouth were obtained. Principal component analyzes were developed to: (i) order the collection points according to their environmental characteristics and (ii) characterize the ecomorphotypes found. Relationships between ecomorphological composition and environmental variables were evaluated by the redundancy analysis, while the indicator ecomorphotype of each condition was identified by indicator species analysis (INDVAL). Rural streams differed from urban ones by the structuring of their environmental components, and even greater distinction between mesohabitats and composition of ecomorphotypes. The greater diversity of habitats along the canal and the presence of riparian vegetation determined the high values of the abundance of nektonic insectivores, with a body shape adapted to the exploration of lentic and more structured environments. Higher velocity of water flow and rockier substrate found in the riffles, selected the groups of benthic invertivores and periphyte substrate scrapers. On the other hand, larger areas of impermeable surface of the urban environment were associated to the homogenization of the canal, and were responsible for selecting ecomorphotypes adapted to the exploration of unstable habitats and native food resources, such as omnivores surface collectors. Therefore, the type of activity developed in the drainage basins of the different water bodies studied had a significant influence on the ecomorphological patterns observed among the fish assemblages, corroborating the hypothesis assumed.